Analysis of Misconceptions on Reproductive System Material in Class XI IPS 2 Students of SMA Negeri 6 Madiun - Rahmawati, Jevi Milda; Nurcahyo, Ima Agung; Primiani, Cicilia Novi (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Conceptual understanding forms the basis of an important component in mastering higher-order thinking skills. This ideal condition is not in accordance with the fact that there are still many students who experience misconceptions. This study aims to determine the level of misconceptions that occur in students of class XI IPS 2 SMA Negeri 6 Madiun. The research method used in this study is descriptive-quantitative with survey techniques. The sample used was 34 students. The results of this study were that 64.7% of students did not understand the process of birth or gestation, 61.8% did not understand the stages of embryo development, 58.8% did not understand the stages of the ovarian cycle, 67.6% experienced misconceptions about the types of material contraception, 52.9% had misconceptions about reproductive system disorders sub-material, 48.5% had misconceptions about oogenesis stages sub-material, 41.2% understood reproductive system disorders sub-material, 38.2% understood spermatogenesis stages sub-material (38.2%), and 38.2% understood the benefits of breastfeeding for mothers and babies.